Mechanized pruning as a recovery strategy for industrial tomato plants damaged by hail at different times of the vegetative cycle - Babelis, German Claudio; Liotta, Mario Alfredo; Pacheco, Daniela; Lund, Santiago; Montenegro, Federico; Recabarren, Agustín; Olguin Pringles, Alfredo (Gobierno de San Juan, 2025)
Poster